THE PROBLEM OF THE RELATIONSHIP BETWEEN PERSONAL FACTORS IN PERSONALITY TRAITS MODELS “BIG FIVE” AND “BLACK TRIAD” - SEROBYAN, ASTGHIK (Bulletin of Yerevan University E: Philosophy, Psychology, 2019)
The Big Five is the most widely used model for the classification of personality traits. However, it is criticized because of describing the positive aspects of the personality, without embracing the negative, dark, antisocial aspects. That is why the Dark Triad model, which reflects the negative aspects of a person, is rapidly developing today. This article aims to examine the relationship between personality traits and the Dark Triad. Linear regression analysis is used. The results indicate that Psychopathy, Narcissism are positive predictors, and Agreeableness is a negative predictor for Machiavellianism. Also, Narcissism is positively predicted by Machiavellianism, Neuroticism, Extraversion, and Openness. Neuroticism, Agreeableness, and Machiavelism are negative predictors for Psychopathy.
Keywords: “Big Five”, “Black Triad”, Machiavellism, Psychopathy, Narcissism, linear regression analysis